Dimensões da adrenal e quantidade de gordura visceral em cães tratados com prednisona - Lopes, Bernardo Fernandes (2011)
The glucocorticoids are widely used in clinical practice, but important adverse effects are described in dog. The aim of this study was to investigate the influence of prednisone on adrenal size and amount of visceral fat in dogs. Images of adrenal ultrasound examinations were edited with the aid of computer program and helical computed tomography as made for quantification of visceral fat in eight healthy young adult dogs immediately before and after 30 days of steroid with therapy prednisone in dose (2mg for each kg, each 24 hours, orally). There was adrenocortical atrophy and increased amount of intra-abdominal fat (p <0.005) between the different experimental time. It was possible to prove the applicability of diagnostic imaging techniques used.